A CASE OF RETROPERITONEAL GIANT LIPOSARCOMA - HASHIMOTO, Shin-ichi; ANDO, Takashi; USUI, Kenji; YAMAGUCHI, Toshiyuki; AKITA, Shingo; KOMATSU, Nobuo (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
A 71-year-old woman seen at another hospital because of flu like symptoms and accidentally pointed out having an abdominal tumor was referred to the hospital. Abdominal CT and magnetic resonance imaging scans offered a suspicion of retroperitoneal liposarcoma, and the patient was operated on. During surgery, the tumor which was yellow in color was present in the retroperitoneum and grew like it compressed the colons involving from the descending to sigmoid colons to the right side. The tumor was covered with capsule like membrane and relatively well-defined from surrounding tissues. The resected tumor was 35×30×20 cm in diameter and 6, 700 g in weight. It was pathologically diagnosed as differentiated liposarcoma. The patient's postoperative course was mostly uneventful. At present, the patient is followed in the outpatient's clinic without no signs of recurrence.